2003
DOI: 10.1208/pt040347
|View full text |Cite
|
Sign up to set email alerts
|

Chemometric evaluation of pharmaceutical properties of antipyrine granules by near-infrared spectroscopy

Abstract: KEYWORDS: agitating granulation, physical properties, near-infrared spectroscopy, chemometrics, principle component regression analysisThe purpose of this research was to apply near-infrared (NIR) spectroscopy with chemometrics to predict the change of pharmaceutical properties of antipyrine granules during granulation by regulation of the amount of water added. The various kinds of granules (mean particle size, 70-750 µm) were obtained from the powder mixture (1 g of antipyrine, 6 g of hydroxypropylcellulose,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 16 publications
1
25
0
Order By: Relevance
“…It is well recognized that a spectral background shift is related to the particle size of samples in the diffuse reflectance method. [13][14][15][16][17][18] Since Otsuka et al 17,18 reported that a background shift was related to a large particle size, more than 50 μm in diameter, the loading vector of PC1 might be related to the particle size or the radius of pores in the tablets. On the other hand, Norris and Williams 16 reported that the slope of the spectral background was proportional to increasing particle size of a fine powder.…”
Section: Theoretical Analysis Of Tablet Hardness Predictionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well recognized that a spectral background shift is related to the particle size of samples in the diffuse reflectance method. [13][14][15][16][17][18] Since Otsuka et al 17,18 reported that a background shift was related to a large particle size, more than 50 μm in diameter, the loading vector of PC1 might be related to the particle size or the radius of pores in the tablets. On the other hand, Norris and Williams 16 reported that the slope of the spectral background was proportional to increasing particle size of a fine powder.…”
Section: Theoretical Analysis Of Tablet Hardness Predictionmentioning
confidence: 99%
“…[13][14][15][16][17][18] The measurement of tablet hardness and predictions are therefore necessary for quality control in the pharmaceutical industry, since sufficient mechanical strength of the preparations is important during both the manufacturing process and transport. There are several reports on measurements of tablet mechanical strength using the NIR method.…”
Section: Introductionmentioning
confidence: 99%
“…Some work has been done in relating the near infrared (NIR) spectrum with tablet hardness, drug stability, tablet coating and particle size of powders [15][16][17][18]. Otsuka et al [19] used NIRS to predict the angle of repose of granules obtained after the granulation process using various amounts of added water using principal component regression (PCR). In the cited work, the authors discuss that the angle of repose is an index to powder flowability and that can be easily predicted by NIRS.…”
Section: Introductionmentioning
confidence: 99%
“…Only a limited amount of tests was performed, which was covering a small range of residual moisture content (0.43-1.06 % w/w). NIR spectroscopy in combination with multivariate data analysis has also been investigated in order to predict the flowability of both powders [20] and granules [21].…”
Section: Introductionmentioning
confidence: 99%